(untitled) (Research, Society and Development, 2020)
The present work aims to evaluate the in silico toxicity of the monoterpene verbenone. The in silico toxicity assessment was performed using the free software AdmetSAR®, through which the following parameters were analyzed: AMES Mutagenic Potential, Acute Oral Toxicity (TOA), Carcinogenic Potential (PC) and Carcinogenicity (Car). Verbenone did not show mutagenic potential by the AMES test, as well as being non-carcinogenic or carcinogenic and on Acute Oral Toxicity, it was classified in category III, according to USEPA data, which means that the LD50 varies between 500-5000mg/kg. Therefore, it is concluded that the monoterpene verbenone is not mutagenic, carcinogenic or carcinogenic and presented a moderate acute oral toxicity index. That is, according to the in silico test, it is a viable substance for use in humans.